A Comparative Analysis of Collaborative Environmental Management of Natural Resources in Sub-Saharan Africa: A Study of Cameroon and South Africa. (June 2019) - Musavengane, Regis; Tantoh, Henry Bikwibili; Simatele, Danny
In Africa, rural communities thrive on social capital and tend to have a number of commonalities that force them to share natural, physical and social resources. It has been a trend in sub-Saharan Africa to have either formal or informal collaborative management agreements to manage common pool resources (CPRs) to accommodate different actors and interests. This paper draws lessons from past and contemporary collaborative schemes in Cameroon and South Africa to enhance the practice and governance processes of natural resources in sub-Saharan Africa in order to promote sustainable development. Using research methods inspired by the tradition of participatory research to collect field-based data and complemented by reflections on previous and existing studies, the paper highlights the importance and benefits of participatory democracy as opposed to representational democracy in co-management of natural resources in rural spaces. It further discusses the need to redefine the roles of national and local governments, the youths and women in ensuring effective participation and the essence of unifying the judicial and culture. To guarantee sustainability of collaborative community-based natural resources, the paper emphasises the role and importance of youth and women empowerment. These issues have been discussed within the broader sustainability discourse.